Synergistic Artemisia monosperma with royal jelly: antibacterial, antioxidant, antibiofilm, and anti-Alzheimer assay - Naglaa Elshafey; Sally Said Ehmedan; Nashwa Hagagy; Shereen M. Elbanna; Reham Z. Sadek (AMB Express)
Abstract This investigation aimed to examine the synergistic effects of fresh royal jelly and local wild Artemisia monosperma leaf extract as antibacterial, antioxidant, antibiofilm, and anti-Alzheimer activity. Gas chromatography-mass spectrometry (GC–MS) identified 16 compounds in Artemisia monosperma, including tricosadiynoic acid, hexadecenoic acid, octadecenoic acid. In contrast, fresh royal jelly contained 13 compounds, including dodecanoic acid, octadecynoic acid, hexadecenoic acid, heptatriacotanol, and their derivatives. The Artemisia monosperma extract exhibited significant antioxidant activity in the DPPH assay, with IC50 value of 5.48 ± 0.002 µg/mL. Fresh royal jelly exhibited an IC50 value of 14.56 ± 0.004 µg/mL. Both substances exhibited significant antibacterial activity in comparison to gentamycin. The Synergistic combination (1:1) effectively suppressed the growth of multidrug-resistant bacterial species, including Bacillus subtilis (ATCC 6633), Enterococcus faecalis (ATCC 10541), Staphylococcus aureus (ATCC 6538), Klebsiella pneumoniae (ATCC 13883), Salmonella typhi (ATCC 6539), and Pseudomonas aeruginosa (ATCC 90274), and decreased biofilm activity. Additionally, in vitro the of inhibition activity (IC50) of the Butyrylcholinesterase enzyme (BChE) for the plant extract, royal jelly and the Synergistic combination were 4.35 ± 0.002 µg/mL, 4.9 ± 0.002 µg/mL, and 3.55 ± 0.002 µg/mL, respectively while the IC50 of rivastigmine (positive control) was 3.9 ± 0.002 µg/mL. in silico analysis reported that the bioactive compounds demonstrated high binding affinities, between − 6.6 and − 10.3 kcal/mol, against the human acetylcholinesterase protein, beside ADMET analysis exhibited high gastrointestinal absorption and potential inhibitory effects on CYP1A2 and CYP2C9 enzymes. Our study indicated that the synergistic effect of Artemisia monosperma and royal jelly bioactive compounds exhibited a promising antibacterial, antioxidant, antibiofilm, and acetylcholinesterase inhibitory activities.